SPECTROPHOTOMETRIC DETERMINATION OF DRUGS AND PHARMACEUTICALS USING KMNO4 AS OXIDANT AND METHYL ORANGE DYE AS ANALYTICAL REAGENT - RAJITHA BALUSANI,; SAYAJI RAO, (International Journal of Pharma and Bio Sciences, 2016)
Simple, sensitive and accurate methods for spectrophotometric determination of five drugs viz., Atrovastatin Calcium, Rosuvastatin Calcium, Sildenafil Citrate, Verapamil Hydrochloride and Amlodopine Besylate has been developed. These methods depend upon the oxidation of the drug by a known excess KMnO4 in sulphuric acid medium and subsequent determination of unreacted KMnO4 with Methyl Orange dye and measuring the absorbance at 507nm. These methods have been validated in terms of LOD, LOQ, precision accuracy, %RSD, robustness and ruggedness. Factors affecting the absorbance viz., concentration of H2SO4 and time of reaction are optimized. The effect of excipients has also been studied and found to have no effect. The calibration curves are found useful for determination of pure drug and can be applied to pharmaceuticals in bulk drug and pharmaceutical industries.